PEMBINAAN TENAGA REKRUITMEN DONOR DARAH DALAM RANGKA MENCEGAH INFEKSI MENULAR MELALUI TRANSFUSI DARAH DI KOTA BENGKULU - Dessy Triana; Elvira Rosana; Mutia Arini Yasrizal (Universitas Bengkulu, 2018)
Thehigh rates of Transfusion-Transmitted Infections (TTI) in Indonesia, especially in Bengkulu Province is quite high and becoming a problem that must be tackled. As reported up to June 2012 the number of cumulative AIDS cases in Indonesia according to gender were 30.931 cases, whilethe cumulative number of HIV and AIDS as many as 611 cases on Bengkulu province.PMI Bengkulu City in 2015 found 61 cases of Hepatitis B, two cases of Hepatitis C and Syphilis 29 cases. WHO Global Database on bloody Safety reported that 20% the population in developed countries as much as 80% have been using donor blood safely, while 80% of the world's population circulating in developing countries only 20% wassafe. The training appliesvarious methods of learning such as: interactive lectures, case relateddiscussions, donor screening practices skills, pre-test and post-test with feedback training. The training was attendedby 14 donor recruitment personnel of UTD PMI Bengkulu with most age range 31 to 40 years old,most of them high school have education level and they have less knowledge and skill. In addition, ongoing education and up-to-date information regarding infectious agent that are potentially transmitted via blood components are crucial for protecting TTI.Keywords: blood transfusion, blood donor recruitment personnel